The Nature and Pathology of Joy and the Obstacle for knowing it from Viewpoint of Ayatollah Javadi Amoli - rouhollah shahmoradian; esmail darabkalai; hosein maghiseh (اخلاق وحیانی)
People intrinsically seek for joy and pleasure, hating toil. Using analytical method, this paper explains the viewpoint of Ayatollah Javadi Amoli   concerning joy, its nature, sorts of it, pathology and obstacles for knowing it. The result is that Ayatollah Javadi Amoli considers joy as comprehension of the proper, and since he is the follower of Mulla Sadra, he thinks that the joy is an existential reality, in contrast to some philosophers considering joy as the lack of pain. He believes that the cognition and elimination of barriers and obstacles of comprehension of the highest joys help human being to have an ethical life accompanied with joy and delight, because attaining joy and pleasure requires attaining the real perfection and closeness to almighty God. Elucidating joy and obstacle to comprehend it, Ayatollah Javadi Amoli intends to pass from corporeal joys to spiritual ones and to closeness to God; it is what has been neglected in the past philosophies. According to him, there is an intimate relation between comprehension of cognitive faculties and multiple worlds, in a way that sensitive joy is associated with comprehension of the sensitive faculty and the human world, and whatever the level of human understanding develops, the comprehension and the sort of joy of that world become higher than that world. From other hand, regarding the comprehension of the higher pleasure and their constancy, the article has indicated that Ayatollah Javadi Amoli contends that if human being endeavors to recognize truly the instances of joys and remove the obstacle, he can reach the more constant and the highest joys.   Having defined the definition of pleasure with his Sadr's viewpoint, the paper divides the pleasure from four different aspects: action and reaction, belonging to the natural world or afterlife, correspondence with reality, and scale of cognition. Considering various theories, the barriers and obstacles of comprehension of the highest joys could be counted as follow: dark, light, hidden, inner, reciprocal, self, the knowledge of the self and intuition. After definition, explaining multiple joys, and obstacle to know it, the article, in its final section, deals with the pathology of the cognition of real instances of pleasure, counting factors like non-purification of the self and ignorance as the most important obstacles of cognition